2009
DOI: 10.1590/s0004-282x2009000600013
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for spasticity among ischemic stroke patients

Abstract: -Spasticity is a determining for functional loss following ischemic stroke. Objective: To detect possible predictive factors for its occurrence. Method: Demographic, clinical and tomographic data on 146 stroke patients were analyzed. Results: Spasticity was noted more frequently among patients who underwent physiotherapy (p<0.0001; OR=19.4; 95% CI: 4.4-84.5), those who underwent such treatment for long periods (p=0.028; OR=4.80; 95% CI: 1.1-8.3) and those with manual work (p=0.041; OR=2.2; 95% CI: 1.02-4.6), l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…541 The prevalence of poststroke spasticity in any limb is in the range of 25% to 43% over the first year after stroke. [542][543][544][545] For patients who require acute rehabilitation after stroke, the prevalence of spasticity in any limb is 42%. 546 The incidence of upper limb spasticity over the first 3 months in patients admitted to rehabilitation is 33%.…”
Section: Spasticitymentioning
confidence: 99%
“…541 The prevalence of poststroke spasticity in any limb is in the range of 25% to 43% over the first year after stroke. [542][543][544][545] For patients who require acute rehabilitation after stroke, the prevalence of spasticity in any limb is 42%. 546 The incidence of upper limb spasticity over the first 3 months in patients admitted to rehabilitation is 33%.…”
Section: Spasticitymentioning
confidence: 99%
“…Patients were admitted to an acute rehabilitation hospital within a one year time period (Age: mean 67. 4,SD 8.33;BMI: mean 29.3,SD 5.91; Length of Stay: mean 7.8 days, SD 1.40). Data was collected to compare fall risk scores and safety for discharge as defined by the FIM.…”
Section: United States Of Americamentioning
confidence: 98%
“…The average age was 38.3 (SD 9.0, range: 26-53). All eleven had received prior medical treatments but reported persistent baseline mean headache level of 9.6 (SD 0.82) with a median of 6 years of duration (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Two veterans finished 10 treatments, four finished 9 treatments, one finished 2 treatments, and four finished less than 5 treatments but were discharged.…”
Section: Referencementioning
confidence: 99%
See 1 more Smart Citation
“…2 The prevalence of spasticity after a first stroke has been inconsistent, ranging between 18% and 38%. [3][4][5][6][7][8] In addition, a recent study indicated that the prevalence of spasticity in patients with stroke referred to the Department of Rehabilitation …”
Section: Introductionmentioning
confidence: 99%